Analisis Peran Tuha Peut Sebagai Pengawas Kinerja Keuchik Suak Puntong Kecamatan Kuala Pesisir Kabupaten Nagan Raya - Julita Julita; Zuhrizal Fadhly (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to study the publics understanding of the duties and functions of the tuha peut as a village apparatus whether it has been implemented as stated in qanun number 5 of 2003 concerning village government or not. If it has been implemented according to the rules, then it needs to be increased again, and if it has not been implemented in accordance with the provisions, it is necessary to find the cause. This study uses descriptive qualitative research methods. Data were obtained through interviews, documentation and literature review relevant to this research. Literature review was conducted to obtain secondary data by studying the literature and applicable laws and regulations. Based on the research results, it is known that the task and role of the tuha peut in the village as a supervisor of the performance of the Suak Puntong keuchik, Kuala Pesisir sub-district, Nagan Raya district has not been carried out as stipulated in the qanun. This is caused by factors that do not establish good cooperation between tuha peut and members, blame each other, unequal information conveyed by tuha peut to members and bring down each other in carrying out their roles and functions as tuha peut. In addition, the supervision of the performance of the keuchik is not currently directed at village development, given the limited budget and widely used for purposes of preventing COVID-19. So that the keuchik program that has been designed is still not running.